2013
DOI: 10.1021/cg401408f
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Characteristics and p-Type to n-Type Transition in Epitaxial NiO Thin Film

Abstract: We were able to systematically control crystallographic characteristics and electrical properties of nickel oxide epitaxial thin films integrated with cubic yttria-stabilized zirconia (c-YSZ)-buffered silicon(001) substrates. The NiO epilayers were grown under several oxygen partial pressures by pulsed laser deposition. The out-of-plane orientation of the NiO layers showed an interesting behavior where it changed from ⟨111⟩ at lower pressures (7 × 10–6 Torr) to ⟨100⟩ at higher pressures (5 × 10–2 Torr). This o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Furthermore, for this sample, the states are widely distributed such that the VRH model applies at all temperatures below 300 K. In contrast to this, for the HT-NiO film, the narrow distribution of states allows charge transfer only between nearest neighbor defects. Based on this model, an explanation can be given why there are some reports on NiO in the literature which claim hole mobilities of more than 1 cm 2 V −1 s −1 , far outside the range typical for polaronic hopping transport [54][55][56][57] . In many of these works, the conductivity of the investigated films is in the range of 1 × 10 −2 S cm −1 and higher, suggesting higher doping levels and thereby a stronger spatial overlap of the ZR wave functions than reported in this work.…”
Section: E Summary Of the Proposed Transport Modelmentioning
confidence: 88%
“…Furthermore, for this sample, the states are widely distributed such that the VRH model applies at all temperatures below 300 K. In contrast to this, for the HT-NiO film, the narrow distribution of states allows charge transfer only between nearest neighbor defects. Based on this model, an explanation can be given why there are some reports on NiO in the literature which claim hole mobilities of more than 1 cm 2 V −1 s −1 , far outside the range typical for polaronic hopping transport [54][55][56][57] . In many of these works, the conductivity of the investigated films is in the range of 1 × 10 −2 S cm −1 and higher, suggesting higher doping levels and thereby a stronger spatial overlap of the ZR wave functions than reported in this work.…”
Section: E Summary Of the Proposed Transport Modelmentioning
confidence: 88%
“…R Moalei et all have reported that the NiO thin films grown at lower oxygen partial pressures behave as n-type and p-type conductivity was observed for the films grown at higher oxygen partial pressures [21]. On the other hand, other research groups have reported both p and n-type conductivity under 9% of oxygen partial pressure and they suggested a p-type conductivity above 9% of oxygen pressure [22].…”
Section: Introductionmentioning
confidence: 96%
“…We would like to point out that, despite the well-known defect chemistry of NiO from earlier studies [45][46][47] suggesting that the main defect species in NiO are Ni vacancies, which are responsible for the p-type conductivity of NiO, the oxygen vacancies are also expected to play an important role at low work-temperatures and low oxygen-pressures. [48] The NiO nanodots in this work were prepared at 500 ℃ and 1.5 Pa oxygen-pressure, which are almost the same with the conditions for NiO films in our previous work, [28] in which the oxygen vacancies in NiO have been observed directly by scanning transmission electron microscopy (STEM).…”
Section: Resultsmentioning
confidence: 97%